Experiences with descriptors for characterization of medicinal and aromatic plants - Pank, F.
Well-defined descriptors are an indispensable tool for management, maintenance and utilization of plant genetic resources. The International Plant Genetic Resources Institute (IPGRI), the International Union for the Protection of New Varieties of Plants (UPOV)and national authorities have published descriptor lists for a great variety of agricultural and horticultural crops, but only for a few species belonging to the group of medicinal and aromatic plants (MAP). Forty years of experiences with the use of descriptors in MAP mainly in the field of breeding research are communicated to support forthcoming efforts in elaborating new descriptors lists. The deliberations focus on some specifics of these minor crops, classifying the descriptors to the following groups: object, experimental data, sample specification, characteristics-growth, development, flower and reproduction biology, cytological traits, molecular traits, biotic and abiotic stress susceptibility, yield, quality differentiated in orphology-dependent quality traits, constituents, sensory quality, and impurities. MAP-specific descriptors are exemplified and the principles of important determination methods are explained. Most of the general available UPOV and IPGRI descriptors are applicable also for MAP.
Keywords: ANALYSIS; BREEDING; DEVELOPMENT; GROWTH; QUALITY; SAMPLE SPECIFICATION; STRESS; YIELD